A survey of sensor devices: use in sports biomechanics. Issue 4 (1st October 2016) - Howard, Róisín M.; Conway, Richard; Harrison, Andrew J.
Abstract: This paper examines the use of sensor devices in sports biomechanics, focusing on current frequency of use of Electromyography (EMG) device preferences. Researchers in the International Society of Biomechanics in Sports were invited to participate in an online survey. Responses on multiple sensor devices highlighting frequency of use, device features and improvements researchers sought in acquisition and analysis methods were obtained via an online questionnaire. Results of the investigation showed that the force platform is the most frequently used device, with inertial measurement units and EMG devices growing in popularity. Wireless functionality and ease of use for both the participant and the practitioner proved to be important features. The main findings of the survey demonstrated need for a simple, low power, multi-channel device which incorporates the various sensors into one single device. Biomechanists showed they were looking for more availability of wireless sensor devices with acquisition and analysis features. The study found there is a need to develop software analysis tools to accompany the multi-channel device, providing all the basic functions while maintaining compatibility with existing systems.